A Critical Study of the Islamic Education Curriculum Development Process in Indonesia - Syahnaz, Assya; Furqan , Muhammad; Amalia, Astrifidha Rahma; Yudabangsa, Adrian (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Curriculum reform in Indonesia continues to evolve in response to rapid scientific, technological, and societal changes. Specific Background: Within this context, Islamic Religious Education (IRE/PAI) requires systematic refinement to ensure its relevance to students’ spiritual, moral, and intellectual development. Knowledge Gap: However, comprehensive analyses that explain how the PAI curriculum is planned, implemented, and evaluated holistically are still limited, particularly regarding the roles of stakeholders in shaping curriculum quality. Aim: This study aims to critically describe the development process of the Islamic Education curriculum in Indonesia through stages of planning, implementation, and evaluation using a qualitative library research approach. Results: The findings show that effective curriculum development requires clarity of goals, understanding of school conditions, recognition of student and teacher needs, identification of existing problems, assessment of teacher competencies, and awareness of social phenomena. The PAI curriculum is developed based on the pillars of iman, Islam, and ihsan, and its success depends on collaboration among administrators, experts, teachers, and parents. Novelty: This study highlights the interconnectedness of curriculum components and stakeholders in a unified development cycle rarely discussed in prior research. Implications: These insights reinforce the need for continuous, context-responsive curriculum development to strengthen the character and competence of learners. Highlights: Curriculum development in Islamic Education must align with societal needs and modern educational demands. PAI curriculum pillars—iman, Islam, and ihsan—serve as the foundation for holistic learner development. Stakeholder collaboration (administrators, experts, teachers, parents) is essential for effective curriculum implementation. Keywords: Curriculum Development, Islamic Religious Education, Planning Process, Implementation, Evaluation